Penyediaan adunan LDPE/LNR melalui penyebaran emulsi = Preparation of LDPE/LNR blend via emulsion dispersion - Rusli Daik,; Yee, Lee Ching, (Universiti Kebangsaan Malaysia, 2007)
Low density polyethylene (LDPE)/ liquid natural rubber (LNR) blends with the composition of 100LDPE/0LNR, 70LDPE/ 30LNR, 60LDPE/40LNR and 40LDPE/60LNR were prepared via dispersion of LDPE and LNR emulsion. LNR was obtained via photochemical sensitization of natural rubber (NR). Emulsion of LNR was prepared by using sodium dodecyl sulfate (SDS) and 1-hexanol as the emulsifier and co- emulsifier respectively. Emulsion of LDPE was prepared in the same way by using LDPE solution in carbon tetrachloride, SDS and 1-hexanol. LDPE/LNR blends were prepared via mixing of LNR and LDPE emulsions. Mechanical properties of the blends were analyzed by tensile, hardness and impact test. Optimum mechanical properties were observed for composite with composition of 60LDPE/40LNR that showed the maximum value of stress and strain. The glass transition temperature, Tg, of the blends as obtained from differential scanning calorimetric (DSC) showed that the blends were homogeneous. Morphology study by using scanning electron microscopy (SEM) also indicates the homogeneity of LDPE/LNR blends produced.